Pengaruh perbedaan jenis benih dan priming terhadap pertumbuhan dan intensitas penyakit bulai pada tanaman jagung - Zakiah Selviani; Titik Nur Aeny; Suskandini Ratih Dirmawati; Yusnita Yusnita; Agustiansyah Agustiansyah (Universitas Lampung, 2026)
This study evaluated the effects of seed type and seed priming on the growth of mays (Zea mays L.) and the intensity of downy mildew disease. The experiment used a factorial Randomized Complete Block Design (RCBD) with a 2 x 4 arrangement, comprising two main factors: seed source (standard seeds and high-zinc content seeds) and priming treatments (no priming, zinc priming, actinomycetes priming, and triple foliar zinc application). The variables observed included plant height, number of leaves, chlorophyll content, and the severity and incidence of downy mildew throughout the growth period. Statistical analysis revealed a significant interaction between seed type and priming treatment on plant growth variables. This interaction had a positive effect on plant growth, indicating that specific combinations of these two factors worked synergistically. Meanwhile, priming treatments using zinc and actinomycetes significantly increased plant height and chlorophyll content, and reduced downy mildew severity, especially during the early growth stages (2–4 weeks after planting). Although seed source alone did not show a significant effect on the observed variables, combinations with certain priming treatments proved effective in enhancing maize plant growth. KATA KUNCI: Aktinomisetes, penyakit bulai jagung, pertumbuhan tanaman, priming benih, seng